The Analisa Efektifitas Sistem Pembelajaran Berbasis E-Learning - Faridatun Nadziroh (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2017)
Nowadays,learning methods needed more inovation to upgrade lesson material for avoid the boredom. Therefore, learning activity based on e- learning system is one of the models with a lot of fitur among others is edmodo, moodle and google classroom. thats models of e- learning system making the student more creative, inovative and independent. at the same times renewal material and learning models by teacher can be allows it can be upgrade the potensial of method. however, with various e-learning system can’t be efective because doesn’t have any integrated with the student also the teacher. Training is needed for teacher to knows and utilize e-learning system with optimal. Keywords : E-Learning, Effective, Innovative.